Control of linear dynamical systems by time transformations - Bodnarchuk, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Necessary and sufficient conditions for the controllability of solutions of linear inhomogeneous integral equations are obtained.